The The Role of Satisfaction as a Mediator of the Influence of Facilities and Location on Revisit Intention: A Study at the Unit Bumi Kepanduan Sentul Bogor - Sudarijati; Dwi Gemina; Selvia, Dina (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: This study examines how facilities and location influence visitors’ intention to revisit the Bumi Kepanduan Sentul Bogor Unit, with customer satisfaction serving as a mediating variable. The research is grounded in the understanding that visitor satisfaction is a key determinant of loyalty and revisit intention, particularly in tourism and recreation destinations. Methods: The study involved 100 respondents selected using a non-probability purposive sampling method. The criteria included visitors aged 17 years and above who had visited the site at least once. A descriptive and verification approach was applied using the path analysis method to determine both direct and indirect effects among variables. Results: The findings reveal that facilities and location have a direct and positive influence on satisfaction, while both also directly affect revisit intention. Furthermore, satisfaction itself significantly influences revisit intention and serves as a mediating factor between facilities, location, and the desire to return. These results indicate that improved facilities and strategic location can enhance visitor satisfaction, which ultimately increases the likelihood of revisits. Conclusion: This study highlights the importance of maintaining and improving facilities and location quality to enhance visitor satisfaction and loyalty. However, the study is limited by its relatively small sample size and narrow variable scope. Future research is recommended to include additional factors such as lifestyle, social influence, and reference groups, as well as to use a larger and more diverse sample to obtain more representative results.